Magnitude and associated factors of preoperative anemia among adult elective surgical patients at Saint Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia, 2024 - Biset, Wondimnew Mersha; Nasser, Nura; Tolu, Lemi Belay; Tsega, Nuhamin Tesfa; Abraha, Mebratu (Frontiers in Medicine, 2024)
BackgroundPreoperative anemia is a common hematologic public health problem among elective surgical patients. Preoperative anemia complications independently increase the risk of perioperative complications and mortality rate. Despite this complication, there is a scarcity of evidence on the prevalence and associated factors of preoperative anemia among adult elective surgical patients in Ethiopia. Therefore, this study aimed to investigate the magnitude and associated factors of preoperative anemia among adult elective surgical patients at Saint Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia.MethodsAn institution-based cross-sectional study was conducted from January 1 to 30, 2024 at Saint Paul’s Hospital Millennium Medical College. A consecutive sampling technique was used to select eligible study participants. Chart review and a structured, pretested, and interviewer-administered questionnaire were employed. Kobo toolbox was used to collect the data and exported to SPSS version 25 software for data cleaning, coding, and analysis. Binary logistic regression model was fitted to identify factors associated with preoperative anemia. An adjusted odds ratio (AOR) with its 95% CI and a p-value of ≤0.05 was used to declare a statistical association.ResultsA total of 247 study participants were included in the analysis, giving a response rate of 98.8%. Majority (68%) of the participants were from urban areas. The median age of the patient was 38 (IQR ± 32) years. The magnitude of preoperative anemia was found to be 27.1% (95% CI: 21.9, 33.1). Being female (AOR = 3.44; 95%CI: 1.53, 7.73), being overweight (AOR = 0.26; 95%CI: 0.10, 0.88), and having infection and injury/trauma as indications for surgery (AOR = 4.59; 95%CI: 1.62, 12.96) and (AOR = 3.58; 95%CI: 1.35, 9.49) were significantly associated with preoperative anemia.ConclusionIn this study, more than one-fourth of the study participants had preoperative anemia. To decrease this public health problem, it is better to screen at risk patients, specifically females and trauma patients during the preoperative visit and disseminate information about a healthy diet and the prevention and treatment of anemia through health education.